Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Penguasaan Konsep dan Keterampilan Proses Sains Fisika Peserta Didik Kelas XI MAN 2 Mataram Tahun Pelajaran 2017/2018 - Putri Kurnia Suwandari; Muhammad Taufik; Satutik Rahayu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
This research is aimed to examine the effect of guided inquiry learning model toward physics studentsÃ¢â¬â¢ concept mastery and science process skills at class XI of MAN 2 Mataram in academic year 2017/2018. This is experiment research with posttest-only control group design. The Population of this research is all students of class XI MIA MAN 2 Mataram. The sampling technique used is purposive and cluster random sampling, which is the students of class XI MIA 5 as experiment and XI MIA 4 as control group. The experiment group was treated with guided inquiry learning model while the control group was treated with conventional learning. Technique of collectig data of the mastery concept using essay test 8 question, the skills of science process using non-test instruments in the form of observation sheets. The hypothesis was tested using manova based SPSS 16.0. The result of manova test showed that there was an effect of guided inquiry learning model toward mastery of concept and skill of science process.